N2O emission reduction in the biological nitrogen removal process for wastewater with low C/N ratios: mechanisms and strategies - Xie, Yawen; Jiang, Cancan; Kuai, Benhai; Xu, Shengjun; Zhuang, Xuliang (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract：Urban wastewater, as the main influent type of Waste Water Treatment Plants (WWTPs), has the characteristic of low carbon to nitrogen ratio (C/N). In the biological nitrogen removal (BNR) process, insufficient carbon source often affects the nitrogen removal efficiency and leads to more N2O emissions. We review recent researches on N2O emissions in the BNR process of wastewater with low C/N. The availability of carbon sources affects heterotrophic denitrification (HD) and autotrophic nitrification/ denitrification processes, which are the main reasons for N2O emissions in BNR. For the sustainable development of BNR in WWTPs, we introduce strategies suitable for reducing N2O emissions in the BNR process of low C/N wastewater from two aspects: traditional process innovation and new process development. These strategies mainly include carbon source addition, adjustment of aeration strategy, optimization of oxidation ditch and biofilm facilities, and application of Anammox related processes. In the future, it is still necessary to further deepen this research direction through the normalization of N2O emission quantification standards, exploration of N2O metabolism mechanisms, assessment of environmental effects of emission reduction strategies, and practical application of new processes.